Beeman, Plain, Honest Men - The Making of the American Constitution - Merriman, Scott (Teaching History: A Journal of Methods, 2011)
Richard Beeman’s work examines, as the title suggests, how the Constitution was made. It is authoritatively researched, as the author surveyed Madison’s writings, those of other contributors, and The Federalist Papers, as well as consulting many other sources. The purpose is twofold: first, to humanize that founding document. Instead of describing it as a "miracle from Philadelphia," as Catherine Drinker Bowen did, Beeman views it more as the work of men. He uses a quotation of Gouverneur Morris for his title, and so himself is not calling the Founding Fathers plain or ordinary. However, if forced to choose between man and god to describe the founders, Beeman, long-time professor at the University of Pennsylvania and author of multiple books, clearly would choose man. Beeman’s second purpose is to wade into the debate about how we interpret the Constitution. This is not in terms of what any specific provision means, but more how certain we can be about how the Founding Fathers (or the founding generation) understood any provision. He argues that it is difficult to tell what they thought would actually happen and notes how many of the provisions were arrived at quickly with little discussion. For instance, the "necessary and proper" clause was agreed to swiftly with no dissenting vote. Thus, about all the current generation can tell is that everyone might have agreed on the meaning, but there is little to tell what that meaning was. He also points out that little discussion was done at the ratification conventions and that various states had external reasons to adopt the Constitution, and so they focused on that (whether or not to join) rather than what the Constitution meant. Turning to The Federalist Papers, he notes that these were more "political propaganda aimed at persuading undecided voters to support the Constitution" than "high-minded political theory." Thus, interpreting them as exactly what the Constitution meant at the time is problematic.